PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV PADA MATERI KELILING DAN LUAS BANGUN DATAR - Enjelina Adriwati; Wara Sabon Dominikus; Adam Bol Nifu Benu (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of the Realistic Mathematics Education (PMR) approach on the mathematics learning outcomes of fourth-grade students on the circumference and area of ​​flat shapes. The research method used is quantitative with a Pre-Experimental Design approach of the One-Group Pretest-Posttest Design type. The sampling technique used a simple random sampling technique. Data on student learning outcomes were collected using a multiple-choice test instrument consisting of 20 questions. This study was analyzed using prerequisite tests in the form of normality and homogeneity tests and hypothesis testing using paired sample t-tests. The results showed that there was a significant influence in the use of the Realistic Mathematics Education approach to the mathematics learning outcomes of fourth-grade students on the circumference and area of ​​flat shapes. This is evidenced by the results of the paired sample t-test with a significance level of 0.05 and a sig. (2-tailed) value of 0.000 <0.05, which means that H₀ is rejected and Hₐ is accepted.